Analisis Tindak Tutur Direktif dalam Pembelajaran Bahasa Indonesia Berlatar Belakang Budaya Jawa di SMP Al Qolam Gemolong - Kusuma, Dian Tyas Adi, Drs. Andi Haris Prabawa, M.Hum (2016)
The use of Indonesian among schools in the learning process is the diversity of languages spoken utterances which have a distinctive style, which has a specific purpose depending on the context of the speech itself. This study has two objectives to be achieved (1) describe how the shape of speech directive teachers and students in the classroom learning backgrounds Javanese culture in junior AL Qolam Gemolong, and to (2) describe the strategy forms of speech directive teachers and students in learning I cultural backgrounds of Java in SMP AL Qolam Gemolong. This research is qualitative descriptive. This study uses the findings form directive speech. The source of the findings are used by the researchers that the recordings in learning activities teachers and students when communicating, while the sources used in this study were teachers and students. Findings collection techniques used in this research is the free technique involved a conversation, see the techniques, recording techniques and technical notes. In this study using triangulation sources. The findings in this study using intralingual match. The results in this study indicate: 1) the form of speech directive teachers and students in the form of a directive asking, pleading, pressing, inviting, encouraging, ordering, suggesting, probing, questioning, interrogating, ordering, 2) strategy speech directive teachers and students in learning activities Indonesian set in Javanese culture in the junior Qolam Gemolong, in the form of speech act strategies direct and indirect speech acts. Keywords: directive, the strategy says